(3GdQSGdI GdOGeZI ddaGSb GdQO Ydi GdfUjQi dYfg Gddgs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj,J (B433 (3g` s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdi SHMGfg GeG HYO CjOce Gdehdi HJCjjOg Gfg hQO Edi cJGH Cdag HYV GdfUjQjI GdcGaQjf HehdGfG Ld PcQg GdeTcQjf Hg acJHJ gPg GdQSGdI QOkG Ydi eG Cdag gPG GdaGSb s
(3BNQgG (B:s
(3abO EbJQHJ GdSGYI hGfTb GdbeQ fYe GdfUjQ GdeYjf JeJ GdQSGdI hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdCdaGX HGdMeQIs
(3QSGdI ef QSGFd GdOQhR s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B79s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds